History of a Half-Arm - Grossman, Sara (Disability Studies Quarterly, 2019)
"History of a Half-Arm" is a piece of creative nonfiction that utilizes fragmentary, often chaotic narrative structures in order to explore the author's experience of living with and without a left-arm prosthetic. The author was born with what the medical community terms a "congenital abnormality of the left forearm" and was first fitted for a prosthetic at 3-months old. "History of a Half-Arm" captures the speaker's daily experience of navigating the world as a physically disabled person who has chosen not to utilize prosthetic technology.